Barbados : First Review under the Extended Arrangement and Request for the Completion of the Financing Assurances Review and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report, 2019)
First Review under the Extended Arrangement and Request for the Completion of the Financing Assurances Review and Modification of Performance Criteria - Press Release; Staff Report; and Statement by the Executive Director for Barbados.